Blending Tradition and Technology: Digital Classroom Pedagogies for the Indian Knowledge System - Saxena, Preeti; Pathak, Chandrang (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The Indian Knowledge System (IKS), with its vast repository of insights in science, philosophy, art, medicine, and ecology, offers rich possibilities for holistic and sustainable education (Deb & Sengupta, 2021; Zarkar, 2010). However, integrating IKS into contemporary classrooms is constrained by limited resources, accessibility challenges, and the absence of systematic pedagogical models.This paper explores how digital tools can transform the teaching and learning of IKS by enhancing engagement, accessibility, and interaction for twenty first century learners (National Education Policy [NEP], 2020). Drawing on emerging practices such as augmented and virtual reality, gamified learning platforms, learning management systems, and digital storytelling, the paper illustrates how ancient Indian texts, practices, and traditions can be presented in immersive and learner centred ways (Lambert, 2013; Prensky, 2001). Particular emphasis is placed on digital storytelling and gamification for teaching classical literature, Indian art forms, linguistics, and Vedic Mathematics. The paper also critically examines key challenges, language barriers, infrastructural inequities, and cultural sensitivity. By highlighting the synergy between technology and traditional knowledge, the paper proposes broad strategies for educators and institutions to integrate IKS meaningfully into digital pedagogy (Indian Knowledge Systems, Vol. 1). Such integration not only contributes to preserving India’s intellectual heritage but also aligns with global shifts towards educational systems that emphasize sustainability, critical thinking, and cultural appreciation (Deb & Sengupta, 2021). IKS pedagogy for a digitally empowered generation can ensure that this timeless knowledge continues to inspire and guide future learners.